2015
DOI: 10.1007/s40496-015-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of PDLSC and Relevance to Periodontal Regeneration

Abstract: Periodontitis, a major chronic inflammatory disease of dental tissue, causes periodontal tissue destruction and alveolar bone resorption. When large amounts of alveolar bone are lost, it is very difficult to regenerate the bone using conventional treatments. Periodontal ligament stem cells (PDLSCs) have attracted much attention as potential cell sources for alternative periodontitis regenerative treatment because of their capacity for self-renewal and multipotency. Recently, PDLSCs were found to possess immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
(65 reference statements)
0
12
1
Order By: Relevance
“…20,37 It was demonstrated that hPDLSCs formed a cementum-like tissue with condensed collagen bers, which consisted of the periodontal ligament. 38 Thus, the transplantation of hPDLSCs was suggested to be a promising alternative cell source to the gold-standard hBMSCs, and hold the promise as a therapeutic approach for the reconstruction of alveolar bone tissues and the periodontal complex. 38 CPC scaffolds are excellent candidates for orthopedic surgical applications due to their excellent biocompatibility, osteoconductivity, degradability, injectability and moldability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,37 It was demonstrated that hPDLSCs formed a cementum-like tissue with condensed collagen bers, which consisted of the periodontal ligament. 38 Thus, the transplantation of hPDLSCs was suggested to be a promising alternative cell source to the gold-standard hBMSCs, and hold the promise as a therapeutic approach for the reconstruction of alveolar bone tissues and the periodontal complex. 38 CPC scaffolds are excellent candidates for orthopedic surgical applications due to their excellent biocompatibility, osteoconductivity, degradability, injectability and moldability.…”
Section: Discussionmentioning
confidence: 99%
“…38 Thus, the transplantation of hPDLSCs was suggested to be a promising alternative cell source to the gold-standard hBMSCs, and hold the promise as a therapeutic approach for the reconstruction of alveolar bone tissues and the periodontal complex. 38 CPC scaffolds are excellent candidates for orthopedic surgical applications due to their excellent biocompatibility, osteoconductivity, degradability, injectability and moldability. However, their poor strength and brittleness have limited their use to primarily low stress-bearing applications.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, GT excision controls bleeding locally and thus contributes to a more efficient debridement of a periodontal osseous lesion while allowing space for the placement of graft materials . In both homeostasis and disease/injury, the perivascular regions in the periodontal ligament are enriched with stem/progenitor cells that can migrate to the wound site, attach to the denuded root surface, proliferate and mature to tissue‐forming cells (osteoblasts, cementoblasts and fibroblasts) and interact with other host cells by releasing regenerative signals, cytokines, growth factors, chemokines, etc . There is growing evidence that GT‐derived MSCs possess high regenerative potential and may be used as autologous transplants for subsequent periodontal reconstructive operations …”
Section: Discussionmentioning
confidence: 99%
“…As a powerful inducer of the progenitor cell proliferation in hard tissue regeneration, in contrast, fibroblast growth factors (FGF-2) would enhance the proliferation while inhibiting terminal differentiation of PDLSCs in vitro [41]. Finally, PDLSCs have an immunomodulatory ability comparable to other MSCs; for instance, allogeneic PDLSCs could enhance periodontal regeneration due to their low immunogenicity and immunosuppressive effects on T cell as well as B cells [42].…”
Section: Functionmentioning
confidence: 99%